Perspektif Dakwah Tentang Cyberbullying - Mochammad Irfan Achfandhy; Fadhil Hardiansyah; Muhajir Muhajir; Umi Maisah (Nizham Journal of Islamic Studies, 2022)
Cyberbullying is a massive act of bullying in cyberspace in the digitalization era. However, da'wah as a social practice of empowering Islamic communities is still lacking in exploring cyberbullying. In response to this, this study aims to elaborate a da'wah study on cyberbullying through the film "Dua Detik". The research method utilizes qualitative research that is explanative. The data source was obtained from the film entitled "Dua Detik" on the Manusia Biasa YouTube channel and the data analysis technique utilizes Multimodal Critical Discourse Analysis (MCDA). The results show that the film "Dua Detik" constructs an anti-bullying discourse to build the mindset and ideology of netizens to collectively oppose bullying. The anti-bullying discourse in accordance with the perspective of transformative da'wah studies includes elements of social orientation, social advocacy, interactive dialogue and stakeholder collaboration.